"Legal Eagle" entrepreneurship education for law students: special reference to International Islamic University Malaysia - Abd Ghadas, Zuhairah Ariff; Muslim, Herna; Hamid, Zarinah (Universiti Putra Malaysia Press, 2014)
In Malaysia, entrepreneurship education in higher learning education is not new. The government has taken great effort to transform the country’s economy into the knowledge-based economy and entrepreneur has been identified as one of the key elements to the development of the knowledge economy. Lots of fund had been allocated by the government to propagate the importance of graduates to become entrepreneurs and less dependent on employers.